Ethanol production from rice straw: Comparative study of single and combined use of CaO/Ag nanocatalyst with Saccharomyces cerevisiae and Aspergillus terreus - Amany M. Hamad; Ahmed A. El-Sherif; Asmaa M. Ahmed; Heba Allah Abdelnabi Eid Mohamed; Engy Shams-Eldin; Maha A. Mohamed; Esraa Ahmed Abu El Qassem Mahmoud; L.M. Kasem; Ahmed E. Ibrahim; Heba M. Fahmy (World Journal of Microbiology and Biotechnology, 2026)
This research investigates a sustainable method for bioethanol synthesis from ammonia-pretreated rice straw utilizing a CaO/Ag nanocatalyst. The addition of ammonia elevated the available cellulose level of rice straw from 37.7% to 55.87%, thereby improving its suitability for enzymatic hydrolysis. The fungal isolate Aspergillus terreus (At PP590607) and the yeast Saccharomyces cerevisiae (Sc OR668931) were utilized both separately and in conjunction, with or without the CaO/Ag nanocatalyst. Antimicrobial testing revealed MICs of CaO/Ag nanoparticles ranging from 1 to 10 µg/ml, with sub-MIC doses employed in subsequent experiments. This nanocatalyst enhanced the liberation of fermentable reducing sugars, especially in conjunction with S. cerevisiae . Nonetheless, it demonstrated a considerable inhibitory effect on the net product of the resulting reducing sugars, from 5.2 mg/L to 3.8 mg/L sugar, when paired with A. terreus . The maximum ethanol output was achieved with S. cerevisiae alone, but silver nanoparticles exhibited slight adverse effects on yeast fermentation. The HPLC and DNS assays measured ethanol and sugar concentrations, respectively, while SEM imaging demonstrated that ammonia pretreatment compromised lignocellulosic architecture, enhancing saccharification. While concurrent saccharification and fermentation with both microorganisms reduced ethanol yields, the incorporation of nanocatalysts markedly improved production. ITS sequencing and BLAST verified the microbial identities with 98.1% and 99.6% similarity for A. terreus and S. cerevisiae , respectively. The research highlights the need to enhance microbe–nanocatalyst interactions to improve fermentation efficiency. It advocates an environmentally sustainable and economically viable method for transforming lignocellulosic agricultural byproducts into renewable bioethanol through integrated microbial and nanotechnological techniques. Graphical abstract Conceptual workflow of bioethanol production from ammonia-pretreated rice straw using Saccharomyces cerevisiae and Aspergillus terreus , with and without CaO/Ag nanocatalyst supplementation.